Lead bioaccumulation in Opuntia ficus-indica following foliar or root exposure to lead-bearing apatite. (January 2017) - El Hayek, Eliane; El Samrani, Antoine; Lartiges, Bruno; Kazpard, Veronique; Aigouy, Thierry
Abstract: The contamination of edible leafy vegetables by atmospheric heavy metal-bearing particles is a major issue in environmental toxicology. In this study, the uptake of lead by cladodes of Opuntia ficus-indica ( Ofi ), traditionally used in Mexican cuisine and in livestock fodder, is investigated after a 4-months exposure of either cladodes or roots to synthetic Pb-fluorapatite particles. Atomic Absorption Spectroscopy (AAS) for the quantitative analysis of Pb levels, Scanning Electron Microscopy coupled with Energy Dispersive X-Ray Spectroscopy (SEM-EDX) for the examination of the cladode surface and fate of particles, and Micro-X-ray fluorescence (μXRF) measurements for elemental mapping of Pb in cladodes, were used. The results evidence that foliar contamination may be a major pathway for the transfer of Pb within Ofi cladodes. The stomata, areoles, and cuticle of cladode surface, play an obvious role in the retention and the incorporation of lead-bearing apatite, thus revealing the hazard of eating contaminated cladodes. The possibility of using series of successive cladodes for biomonitoring the atmospheric pollution in arid and semi-arid regions is also rapidly discussed. Graphical abstract: Highlights: Opuntia ficus-indica readily bioaccumulates Pb by both foliar and root pathways. The Pb contamination level is significantly higher following foliar exposure. The structure of cladodes surface facilitates the integration of airborne particles. The toxicological risk of Pb accumulation in nopalitos should be emphasized. Abstract : The successive cladodes of Opuntia ficus-indica can be used for biomonitoring of atmospheric pollution.